STUDI KOORDINASI DEWAN KETAHANAN PANGAN PROVINSI KALIMANTAN TIMUR KEPADA DEWAN KETAHANAN PANGAN KABUPATEN DAN KOTA DALAM MENJAGA KETAHANAN PANGAN DAERAH - Abd Rachim AF; Zulkifli (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
Food in everyday life is a basic need.Without the fulfillment of food, of course it cannot grow and develop properly. Given that most of the availability of nutritional intake is obtained from various types of food sources. Starting from rice, vegetables, fruits, side dishes, milk to meat andfish. In East Kalimantan Province there is a Food Security Council (DKP) of East Kalimantan Province as a Food Security Working Group Team at the East Kalimantan Province level and builds synchronization and harmonization of food security with Regency/City DKP, through planned and implemented coordination as stated in the Governor's Regulation East Kalimantan Number 12 of 2017 concerning the Establishment of the East Kalimantan Provincial Food Security Council. The purpose of the study was to determine theform and aspects relating to the coordination of the DKP of East Kalimantan Province to the DKP of the Regency and City in Maintaining Regional Food Security. This study uses qualitative research methods with descriptive nature, with data analysis using the Interactive Model Data Analysis from Miles, Huberman, and Saladana (2014). The results showed that the coordination occurred in a vertical and horizontal pattern. The vertical context is of course the coordination carried out by the DKP of the East Kalimantan Provincial Government to the Regency/City DKP, and vice versa. While horizontal coordination in order to support vertical coordination.